Promoting Equity in Higher Education through Scholarships: Evidence from Developed and Developing Countries - Michaela Mhagama (Action Research Journal Indonesia (ARJI), 2026)
Scholarships have emerged as important policy instruments for promoting equity in higher education by reducing financial barriers and expanding opportunities for students from disadvantaged and underrepresented backgrounds. This study examines the role of scholarships in enhancing educational equity and draws lessons from global and Tanzanian experiences. A systematic literature review (SLR) methodology was employed to identify, evaluate, and synthesize evidence from peer-reviewed journal articles, policy reports, and institutional publications retrieved from Google Scholar, Scopus, Web of Science, ERIC, and reports published by international organizations. The review followed a systematic process of identification, screening, eligibility assessment, and thematic synthesis. Studies published in English between 2020 and 2025 that examined scholarships, financial aid, educational access, student retention, graduation, and social inclusion in higher education were included. Duplicate records, conference abstracts, editorials, newspaper articles, studies focusing on primary and secondary education, and publications lacking sufficient methodological information were excluded. The findings reveal that scholarships significantly increase access to higher education for students from low-income families, women, rural communities, ethnic minorities, and other marginalized groups. Beyond improving enrolment, scholarships contribute to student retention, academic success, graduation rates, and social mobility. However, challenges such as inadequate funding, limited awareness, bureaucratic application procedures, and inequitable distribution continue to undermine their effectiveness. The review concludes that scholarships remain a critical mechanism for advancing educational equity, but their impact can be strengthened through increased investment, transparent allocation systems, targeted support for vulnerable groups, and complementary interventions such as mentorship, academic support, and career guidance. This study offers policy insights for strengthening equitable participation in higher education, particularly in developing-country contexts such as Tanzania